(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The aim of current work was study the relationship of Helicobacter pylori bacteria to anemia. Samples were collected from the Endoscope Unit for the period from 12/14/2022 to 1/30/2024 at Azadi Teaching Hospital and Al-Watan Al-Ahli Hospital in Kirkuk Governorate, from both sexes for the age group (14-57) years. Stool samples were taken from the same patients Those undergoing laparoscopy for the purpose of investigating the presence of Helicobacter pylori, as well as blood samples for the purpose of performing a complete blood count (CBC) analysis. Tissue biopsy samples were taken by the gastroenterologist using laparoscopic forceps, and (88) samples were obtained from these patients, with two tissue biopsies from each patient. Males were 38% (17) and females were 62% (27). Their ages ranged from (14-57) years. As for the control group, it included (44) healthy individuals and those negative for Helicobacter pylori. The results of the research for all individuals included in the study, after performing a complete blood analysis, showed a significant decrease in the number of red blood cells, the concentration of hemoglobin, the size of agglutinated blood cells, as well as the platelet count for the age groups of people infected with the bacteria with the same age groups for the control groups, which demonstrated the presence of a strong association between Helicobacter pylori infection and poverty. Blood represented by a decrease in the number of red blood cells and the concentration of hemoglobin and platelets, while the study and the results of the complete blood analysis showed a significant (P,0.05) increase in the number of platelets and the count of white blood cells for the same previous age groups compared to the control groups, where a high rate of sedimentation of red blood cells is an indicator of the presence of inflammation. In the body, a high rate of white blood cells indicates a systemic humoral immune response against bacterial infection.